Phases and Steps in the Access to Data in Information Tools - Bergenholtz, Henning; Bothma, Theo J.D.; Gouws, Rufus H. (Lexikos, 2015)
In the information society, it is much easier for someone to find relevant data if s/he has an information need because of the availability of databases and electronic information tools. In information science this topic is usually treated under the topic information behaviour. In lexicography the term access process is used (Bergenholtz and Gouws 2010). It can be shown that this process beginning with the "origin of the problem" leading to an "information source usage situation" contains different parts, and that each part contains different phases, with the pre-consultation phase and the intra-consultant phase containing different steps. The most important concepts here are the access route and the access time. In this paper some experiments in two case studies are described to show how different access processes in different user situations take place.